The C‐terminus of amelogenin enhances osteogenic differentiation of human cementoblast lineage cells. (5th May 2016) - Kunimatsu, R.; Yoshimi, Y.; Hirose, N.; Awada, T.; Miyauchi, M.; Takata, T.; Li, W.; Zhu, L.; Denbesten, P.K.; Tanimoto, K.
Abstract : Background and Objectives: Amelogenin proteins are the major constituent of developing extracellular enamel matrix and are believed to have an exclusively epithelial origin. Recent studies have suggested that amelogenins might induce the differentiation and maturation of various cells, including cementoblast lineage cells. However, the residues comprising the active site of amelogenin remain unclear. The purpose of this study was to identify the active site region of amelogenin by studying the effects of amelogenin fragments on the osteogenic differentiation of cementoblasts. Material and Methods: Amelogenin fragments lacking the C‐terminus (rh163) and N‐terminus (rh128) and a fragment consisting of the C‐terminal region of rh174 (C11 peptide) were synthesized and purified. Human cementoblast lineage cells were cultured in osteogenic differentiation medium and treated with 0, 10, 100 or 1000 ng/mL of rh163, rh128 or C11 peptide. The mRNA levels of bone markers were examined by real‐time polymerase chain reaction analysis. Alkaline phosphatase activity and calcium deposition were also determined. Mineralization was evaluated by alizarin red staining. Results: The osteogenic differentiation of human cementoblast lineage cells was significantly enhanced by treatment with rh128 or C11 peptide, whereas rh163 had no significant effect as compared with untreated controls. Conclusions: The C‐terminus of amelogenin promotes the osteogenic differentiation of human cementoblast lineage cells, indicating the possible utility of C11 peptide in periodontal tissue regeneration.